IMPLEMENTASI PEMBELAJARAN KOOPERATIF PADA PEMBELAJARAN IPS DENGAN METODE THINK-PAIR-SHARE DI SD 02 SUNTU KOTA BIMA - Aulia, Rasti; Astianti, Desy; Nurjaimah, Nurjaimah; Nurfahraini, Nurfahraini; Putri, Nadia (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2024)
Less attractive and non-interactive teaching approaches often make students feel bored and less motivated to learn. Using traditional methods such as lectures without actively involving students can reduce student interest and participation in learning. This is due to the lack of creativity and innovation of teachers in creating and providing learning media that can enhance students' interest and incentives for learning. The aim of this study is to find out how the cooperative learning model of Think Pair Share is used and how it affects students' understanding. This research uses a type of qualitative research, which means a series of research that includes essential elements such as observations, interviews, and documentation for data collection. Students at SD 02 Suntu City Bima have experienced an improvement in their learning process. From less active, quiet, and low-thinking students, they now become more active students, dare to stand in front, and have strong thinking during their learning process. This is the result of teachers using the cooperative learning model Think Pair Share.